CALCULUS OF A SINGLE VARIABLE : CALCULUS OF A SINGLE VARIABLE : CalcChat and CalcView - Larson, Ron; Edwards, Bruce H., 1946- (Cengage, 2024)
"Designed for the three-semester engineering calculus course, CALCULUS OF A SINGLE VARIABLE: EARLY TRANSCENDENTAL FUNCTIONS, 8th Edition, offers instructors and students innovative teaching and learning resources. The Larson team clearly defines and demonstrates concepts and rules of calculus for students -- and offers comprehensive teaching resources for instructors that employ proven pedagogical techniques and save time"--